The effect of gold kiwifruit consumed with an iron fortified breakfast cereal meal on iron status in women with low iron stores: A 16 week randomised controlled intervention study - Coad Jane; Kruger Rozanne; Conlon Cathryn; Beck Kathryn; Stonehouse Welma (BMC, 2010)
Abstract Background Dietary treatment is often recommended as the first line of treatment for women with mild iron deficiency. Although it is well established that ascorbic acid enhances iron absorption, it is less clear whether the consumption of ascorbic acid rich foods (such as kiwifruit) with meals fortified with iron improves iron status. The aim of this study is to investigate whether the consumption of ZESPRI® GOLD kiwifruit (a fruit high in ascorbic acid and carotenoids) with an iron fortified breakfast cereal meal increases iron status in women with low iron stores. Methods/Design Eighty nine healthy women aged 18-44 years with low iron stores (serum ferritin (SF) ≤ 25 μg/L, haemoglobin (Hb) ≥ 115 g/L) living in Auckland, New Zealand were randomised to receive an iron fortified breakfast cereal (16 mg iron per serve) and either two ZESPRI® GOLD kiwifruit or a banana (low ascorbic acid and carotenoid content) to eat at breakfast time every day for 16 weeks. Iron status (SF, Hb, C-reactive protein (CRP) and soluble transferrin receptor (sTfR)), ascorbic acid and carotenoid status were measured at baseline and after 16 weeks. Anthropometric measures, dietary intake, physical activity and blood loss were measured before and after the 16 week intervention. Discussion This randomised controlled intervention study will be the first study to investigate the effect of a dietary based intervention of an iron fortified breakfast cereal meal combined with an ascorbic acid and carotenoid rich fruit on improving iron status in women with low iron stores. Trial registration ACTRN12608000360314